Preparation of High-Performance CdS@C Catalyst Using Cd-Enriched Biochar Recycled From Plating Wastewater - Xing, Rui-Zhi; Li, Jia-Xin; Yang, Xing-Gui; Chen, Ze-Wei; Huang, Rong; Chen, Zhi-Xuan; Zhou, Shun-Gui; Chen, Zhi (Frontiers in Chemistry, 2020)
Biochar is widely used for the adsorptive removal of Cd from water and soil, but the produced Cd-enriched biochar carries a risk of secondary pollution. In this work, biochar derived from rice straw was used to adsorb Cd from plating wastewater. The Cd-enriched biochar showed a saturated adsorption capacity of about 63.5 mg/g and could be recycled and used in a mesoporous carbon-supported CdS (CdS@C) photocatalyst after pyrolysis carbonization and a hydrothermal reaction. The results demonstrated that the as-prepared CdS@C photocatalyst contained mixed cubic and hexagonal CdS phases, with a considerably lower band gap (2.1 eV) than pure CdS (2.6 eV). CdS@C exhibited an enhanced photocatalytic performance for the degradation of organic dyes under visible light irradiation compared with pure CdS due to its excellent light-harvesting capacity and efficient electron-hole separation. Moreover, the continuous formation of active species (h+, •OH, and O2•−) was responsible for the photodegradation of organic dyes using CdS@C. This work provides new insights for the safe disposal of Cd-enriched wastewater and for improving the economic viability of Cd-contaminated resources by recovering a value-added photocatalyst.